The Wicked Priest’s Day of Atonement Assault Revisited - Tropper, Amram (Zutot, 2018)
Pesher Habakkuk tells an enigmatic story about the Wicked Priest who caused the Righteous Teacher and his followers to stumble one Day of Atonement. Shortly after the pesher was discovered, Shemaryahu Talmon offered an interpretation of this story that most scholars have accepted. According to Talmon, the Wicked Priest’s opposition to unsanctioned calendars prompted him to prevent the Righteous Teacher and his followers from observing the Day of Atonement on its rightful day in their dissident calendar. Though widely accepted, I maintain that this calendrical interpretation finds little support in the pesher and, therefore, its broad appeal is puzzling. Furthermore, I propose that Talmon’s calendrical interpretation and its popularity are highly indebted to a famous rabbinic story of a calendrical dispute. In the hopes of illuminating the pesher’s cryptic account, modern scholars retrojected a rabbinic plot into the pesher’s narrative, thereby remaking the pesher in the image of the rabbis.